Leveraging Mind Maps For Information Retrieval: A Conceptual Framework For Managing Diversity And Enhancing Expert Searches (Journal of Namibian Studies : History Politics Culture, 2023)
Mind maps are a versatile tool utilized by millions of individuals across various disciplines. In this paper, we explore how information retrieval from mind maps can be employed to manage and embrace diversities. Mind maps serve multiple purposes, such as generating, visualizing, structuring, and classifying ideas. They act as a powerful aid in activities like studying, organizing information, solving problems, facilitating discussions, and drafting written content. For instance, the words and concepts within a mind map can be analysed to create a skill profile of its author, thereby enhancing expert searches by identifying the individual’s expertise based on their mapped ideas. As this is a research-in-progress paper, we do not present empirical research results. Instead, we introduce conceptual ideas and frameworks for further exploration in the domain of information retrieval from mind maps.